New Iterative Manner Involving Sunny Nonexpansive Retractions for Pseudocontractive Mappings - Yaqin Zheng; Jinwei Shi (Abstract and Applied Analysis)
Iterative methods for pseudocontractions have been studied by many authors in the literature. In the present paper, we firstly propose a new iterative method involving sunny nonexpansive retractions for pseudocontractions in Banach spaces. Consequently, we show that the suggested algorithm converges strongly to a fixed point of the pseudocontractive mapping which also solves some variational inequality.